Condition monitoring of thermal comfort and energy efficiency for indoor environment of buildings - Chua, Andy Bing Zhong (2017)
Singapore had successfully positioned herself as one of the top financial centres in the world. Along with aspirations to be a ‘smart city’, energy demands have been on an upward trend and is projected to continue over the next decade. In Singapore, 57% of energy consumed by an indoor building is consumed by the HVAC system with 52% being consumed by the airconditioning system. The purpose of this study is to model, simulate and analyse the performance of the different cooling methodologies. Performance factors encompass energy consumption, zone conditions and thermal comfort index. In this study, various popular cooling methodologies were modelled and simulated using TRNSYS. Results from TRNSYS were compiled and analysed using Microsoft Excel. The cooling methodologies investigated were the vapour compression refrigeration system (VCRS), vapour absorption refrigerant system (VARS) and solid desiccant cooling system (SDCS). A 4-storey building was modelled using SketchUp and imported to TRNSYS using the TRNBuild plugin to be used as a cooling zone. In the context of this study, the vapour compression refrigeration system consumed the least amount of energy per annum and resulted in the lowest amount of total costs per annum. This further reinforces the fact that the vapour compression refrigeration system is the most widely used cooling method for building environments. From the results, it was noted that more than 90% of the energy consumed by the vapour absorption refrigeration system and the solid desiccant cooling system was consumed for heating. Hence, significant savings in energy and costs can be achieved in a scenario where there is available waste heat from industrial plants to provide district cooling to the neighbouring office buildings. Examples of such scenarios are industrial parks like Tuas and Jurong Island. In such scenarios, the solid desiccant system can achieve a total cost that is 59.4% lower than the vapour compression system over a 10-year period. Vapour absorption systems are also able to achieve total costs which are lower than the vapour compression system.